Antimicrobial policy. Imperative need in the face of growing microbial resistance today - Miguel Angel Serra Valdes (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction: Antimicrobials are one of the most pharmacological groups used in the clinical practice, and its relation to microbial resistance is demonstrated. The rational use of antibiotics can be beneficial from the social and medical point of view, but occasionally, their use is not the most correct one and there should be a systematic and special surveillance. A rational antimicrobial policy is necessary in the health care centers. Objective: To review national and international consensuses and criteria on antimicrobial policy to try to unify criteria and apply them the most uniform way possible in health care centers. Material and method: A bibliographic review on antimicrobial policy, antibiotics commission, and antibiotics policy was made in different databases; some of them were: Clinical Evidence, The Cochrane Library, PUBMED, Academic Google, MEDLINE, LIS, Scielo, Medscape, LILACS, Latindex, HINARI, MEDIGRAPHIC-NEWS, NIH Reporter, Scholar Google, and the Web sites of the PAHO/ WHO. Development: Concepts on different Cuban publications, international consensuses, human components, objectives, functions, resources, methods, strategies, and controls were considered. Conclusions: The implementation of any therapeutic modification in the medical attention has to be analyzed correctly in all its dimensions: scientific, technological, and social ones.  When the microbiological study is not possible or there is no antibiogram, the selection of the antibiotic should be made on the local epidemiological and clinical basis. The creation of an Antimicrobial Policy with all its components, resources, and methodology is needed now more than ever. It can be submitted to modifications with new evidences, but it has to be fulfilled to reduce both microbial resistance and the costs, and obtain better results. Keywords: Antimicrobial policy, antibiotics policy, antibiotics commission, microbial resistance, health actions.